Detection of circulating tumor cells in cervical cancer using a conditionally replicative adenovirus targeting telomerase‐positive cells. Issue 1 (9th December 2017) - Takakura, Masahiro; Matsumoto, Takeo; Nakamura, Mitsuhiro; Mizumoto, Yasunari; Myojyo, Subaru; Yamazaki, Rena; Iwadare, Jyunpei; Bono, Yukiko; Orisaka, Shunsuke; Obata, Takeshi; Iizuka, Takashi; Kagami, Kyosuke; et al.
Abstract : Circulating tumor cells (CTC) are newly discovered biomarkers of cancers. Although many systems detect CTC, a gold standard has not yet been established. We analyzed CTC in uterine cervical cancer patients using an advanced version of conditionally replicative adenovirus targeting telomerase‐positive cells, which was enabled to infect coxsackievirus‐adenovirus receptor‐negative cells and to reduce false‐positive signals in myeloid cells. Blood samples from cervical cancer patients were hemolyzed and infected with the virus and then labeled with fluorescent anti‐CD45 and anti‐pan cytokeratin antibodies. GFP (+)/CD45 (−) cells were isolated and subjected to whole‐genome amplification followed by polymerase chain reaction analysis of human papillomavirus (HPV) DNA. CTC were detected in 6 of 23 patients with cervical cancers (26.0%). Expression of CTC did not correlate with the stage of cancer or other clinicopathological factors. In 5 of the 6 CTC‐positive cases, the same subtype of HPV DNA as that of the corresponding primary lesion was detected, indicating that the CTC originated from HPV‐infected cancer cells. These CTC were all negative for cytokeratins. The CTC detected by our system were genetically confirmed. CTC derived from uterine cervical cancers had lost epithelial characteristics, indicating that epithelial marker‐dependent systems do not have the capacity to detect these cells in cervical cancer patients. Abstract : Circulating tumor cells from cervical cancer patients were detected by conditionally replicative adenovirus targeting telomerase‐positive cells. They were HPV‐positive which was identical with their primary lesions and lacked expression of cytokeratins.